High-frequency dynamics of pH, dissolved oxygen, and temperature in the coastal ecosystems of the Tanga-Pemba Seascape: implications for upwelling-enhanced ocean acidification and deoxygenation - George, Rushingisha; Job, Samson; Semba, Masumbuko; Monga, Elinasi; Lugendo, Blandina; Tuda, Arthur Omondi; Kimirei, Ismael (Frontiers in Marine Science, 2024)
Ocean acidification, deoxygenation, and warming are three interconnected global change challenges caused by increased anthropogenic carbon emissions. These issues present substantial threats to marine organisms, ecosystems, and the survival of coastal communities depending on these ecosystems. Coastal upwelling areas may experience significant declines in pH, dissolved oxygen (DO), and temperature levels during upwelling events, making marine organisms and ecosystems in these areas more susceptible to ocean acidification and deoxygenation. Understanding the dynamics of pH, DO, and temperature in coastal upwelling areas is essential for evaluating the susceptibility of resident organisms and ecosystems to lower pH and DO conditions occurring during upwelling events. To accomplish this, we used the pH and the DO loggers to measure high-frequency data for pH and DO, respectively, over six months in the open ocean and for a 24-hour cycle within the mangrove, seagrass, and coral reef ecosystems of the Tanga-Pemba Seascape (T-PS) during the northeast monsoon season. Our findings revealed the occurrence of multiple upwelling events, with varying durations, that result in significant declines in pH, DO, and temperature within the seascape. This is the first study to confirm the occurrence of multiple upwelling events in the T-PS. Moreover, the study has revealed a pH threshold value of 7.43 for ocean acidification in the T-PS. This is the first study to report a threshold value for ocean acidification in coastal upwelling areas of the Western Indian Ocean (WIO). Furthermore, it revealed that the extremely low levels of pH that occurred during upwelling events were above the pH threshold value of 7.43 for ocean acidification, while the extremely low levels of DO fell below the oxygen threshold value of 4.6 mg/L for deoxygenation. During upwelling events, seagrass and coral reef ecosystems, but not mangrove ecosystems, demonstrated elevated mean hourly values of pH and DO compared to those of the open ocean. These findings show that marine organisms and ecosystems in the T-PS are frequently exposed to lower pH and DO conditions due multiple upwelling events. However, their susceptibility to these conditions is reduced to some extent by the presence of seagrass meadows within these interconnected systems.